Profile of early neonatal mortality in Pernambuco and potential for avoidability (Research, Society and Development, 2020)
Objective: To analyze the profile of neonatal mortality in the state of Pernambuco from 2013 to 2017 and its potential for avoidability. Methods: Cross-sectional study, with a population of 4,997 deaths occurring from 0 to 6 days of life. The data came from the Live Birth Information System and the Mortality Information System. For descriptive analysis, the SPSS program was used. The analysis of the potential for avoidance of deaths was carried out according to the “Brazilian list of causes of preventable deaths from interventions by the Unified Health System in children under five”. Results: Deaths predominated in male newborns (56.06%), premature (74.87%) and with extremely low birth weight (42.4%). Among early neonatal deaths, 76.19% were classified as preventable, through effective health actions during care for women during pregnancy, childbirth and care for the newborn. Conclusions: There was a high rate of deaths from preventable causes, especially among premature and extremely low birth weight infants, which could be reversed with the provision of quality perinatal care.